Pengaruh Kompetensi Sosial Guru Pendidikan Agama Kristen Terhadap Moralitas Siswa Kelas VII SMP Negeri 1 Laguboti Tahun Pelajaran 2024/2025 - Sartika Afrida Padang; Tahadodo Waruwu; Sabar Rudi Sitompul; Maria Widiastuti; Sandy Ariawan (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2024)
The aim of this research is to determine the influence of PAK teachers' social competence on the morality of class VII students at SMP Negeri 1 Laguboti for the 2024/2025 academic year. The method used in this research uses quantitative, descriptive and inferential research methods. The population, namely all Protestant Christian students in class VII of SMP Negeri 1 Laguboti for the 2024/2025 academic year, totaled 199 people and a sample of 50 people was determined, namely 25% of the population using a simple random sampling technique. Data was collected using a positive closed questionnaire with 40 items. The results of data analysis show that there is an influence of the social competence of PAK teachers on the morality of class VII students of SMP Negeri 1 Laguboti for the 2024/2025 academic year: 1) Test the analysis requirements: a) positive relationship test obtained by the value rxy = 0,433 > rtabel(=0,05,n=50) = 0,297 thus it is known that there is a positive relationship between variable X and variable Y. b) Testing a significant relationship obtained a value of thitung= 3,333 > ttabel(=0,05,dk=n-2=48)= 2,021 thus there is a significant relationship between variable X and variable Y. 2) Test the effect: a) Test the regression equation, obtained the regression equation =46,75+0,26X. b) Regression coefficient of determination test (r2) = 18,8%. 3) Test the hypothesis using the F test to obtain Fhitung > Ftabel=(=0,05), dk numerator k=20,dk denominator=n-2=50-2=48) namely 11,08 > 1,51. Thus, Ha, that is, there is an influence of the social competence of PAK teachers on the morality of class VII students at SMP Negeri 1 Laguboti for the 2024/2025 academic year is accepted and H0 is rejected.